Do social motivations predict addiction to social media in young people? The role of flow and algorithm awareness - Wang, Xin; Guo, Yin (Anales de Psicología / Annals of Psychology, 2024)
Addictive use of social media has become an increasingly relevant phenomenon among young people, affecting both their psychological well-being and their online behavior. The principal objective of this study is to investigate the associations between addictive use of social media, usage motivations, flow, and algorithm awareness. Our hypothesis is that the flow experience and the algorithm awareness are two mediators through which relevant social motivations influence the development of an addiction to social media. Validated questionnaires are used to measure the study variables, including the BSMAS to assess social media addiction. Structural equation modeling (SEM) with Bootstrap tests is used for analyzing data that is collected from a sample of 580 younger users aged 18 to 22 in China (M = 20.61, SD = 1.32), with 47.7% women and 52.2% men, all undergraduate students, in order to test the research hypotheses. The results reveal that different addiction mechanisms implicate different associations with socially relevant motivations. It advances the field of addiction to social media by showing that addiction is also related to algorithm awareness, through which a new alternative mechanism of addiction is identified.